Vibronic coupling in quantum wires: applications to polydiacetylene - Yamagata, H; Spano, F C (The Journal of chemical physics, 2011)
A theory describing vibronic coupling in direct band gap, one-dimensional semiconductors is developed to account for the photophysical properties of isolated, defect-free conjugated polymers. A Holstein-like Hamiltonian represented in a multi-particle basis set is used to evaluate absorption and emission due to Wannier-Mott excitons. The photophysical properties of such quantum wires are shown to strongly resemble those of Frenkel exciton J-aggregates. The 1(1)B(u) exciton coherence length and effective mass are readily determined from the ratio of the 0-0 and 0-1 line strengths, I(0 - 0)/I(0 - 1), in the photoluminescence spectrum. I(0 - 0)/I(0 - 1) is shown to follow a T(-1/2) dependence, in an excellent agreement with experiments on the red-phase of polydiacteylene.